THE ENVIRONMENTAL OF CRIMINAL LAW ENFORCEMENT BASED ON PANCASILA’s JUSTICE - Sumarno Sumarno; Ismaidar Ismaidar (Jurnal Pembaharuan Hukum, 2023)
The environmental problems can no longer be said to be purely natural problems, because humans provide a very significant causative factor for environmental events. The purpose of this research is to find out and analyze environmental criminal law enforcement based on Pancasila justice, which is a legal concept that upholds the values of justice, equality and humanity. the approach method used in this study uses a normative juridical approach, the resulting research results state that the 2009 Environmental Protection and Management Law defines a crime as an act that can result in exceeding ambient air quality standards, water quality standards, seawater quality standards, or standard criteria for environmental damage. Enforcement of environmental criminal law based on Pancasila justice is a legal concept that upholds the values of justice, equality and humanity.